Analysis of job opportunities for ex-combatants from a business sector perspective - Sandoval-Paucar, Giovanny; Arango-Ospina, Alexandra; Rodríguez-Vélez, Patricia; Santana-Oviedo, Millerlandy (Sociedad y Economía, 2020)
The following article analyzes the perceptions of entrepreneurs in the cities of Palmira, Florida, Candelaria and Pradera (Colombia) regarding the hiring of ex-combatants in their companies. The methodology used is a stratified sampling and a multinomial logit model to examine the appreciations of entrepreneurs. As a result, it is obtained that the attitudes of the business sector are polarized in terms of the employment of ex-combatants. Similarly, perceptions regarding the peace process have a negative effect on the decision when hiring ex-combatants, while perceptions on government incentive policies show a positive effect on this decision.